Relationship between adolescent gaming addiction and myopia, ocular surface condition, and health status: a questionnaire based cohort study - Xiao-Yu Wang; Jin-Yu Hu; Qian-Ming Ge; Cheng Chen; San-Hua Xu; Qian Ling; Yan-Mei Zeng; Wan-Ting Yao; Hong Wei; Jie Zou; Liang-Qi He; Yan Lou; et al. (Scientific Reports)
Abstract This study explores the relationship between gaming addiction among Chinese adolescents and their myopia, ocular surface conditions, and overall health. A cross-sectional questionnaire-based cohort study included 835 participants aged 13–17, selected from 3300. Tools included the Hospital Anxiety and Depression Scale (HADS), Van Dream Anxiety Scale (VDAS), 36-Item Short-Form Health Survey (SF-36), Ocular Surface Disease Index (OSDI), Internet Addiction Test (IAT), and Internet Gaming Disorder Scale-20 (IGD-20). Linear regression, Pearson correlation, and unpaired t-tests were used. Gaming addiction correlated with worsened physical and mental health. Older age and longer gaming duration were linked to higher myopia rates. Males scored higher on HADS, VDAS, IAT, and IGD-20 but lower on SF-36 than females. Myopic gamers had longer gaming durations and higher IAT scores. IGD-20 scores for gamers playing 5–6+ hours daily showed stronger correlations with HADS, VDAS, and OSDI. Online gaming significantly impacts vision, physical and mental health, and ocular surface conditions. Score differences between groups underscore the need for interventions, including mental health support, cognitive-behavioral correction, and preventive eye care.